2011
DOI: 10.1523/jneurosci.6461-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Spatial Acuity Enhancement in Blindness: Evidence for Experience-Dependent Mechanisms

Abstract: Tactile spatial acuity is enhanced in blindness, according to several studies, but the cause of this enhancement has been controversial. Two competing hypotheses are the tactile experience hypothesis (reliance on the sense of touch drives tactile-acuity enhancement) and the visual deprivation hypothesis (the absence of vision itself drives tactile-acuity enhancement). Here, we performed experiments to distinguish between these two hypotheses. We used force-controlled grating orientation tasks to compare the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
120
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(138 citation statements)
references
References 65 publications
9
120
1
8
Order By: Relevance
“…For instance, prior studies have shown that tactile finger acuity can increase in normal sighted individuals through intensive training (Sathian and Zangaladze, 1997;Harris et al, 2001), suggesting that blindness may only act as a facilitator in the development of increased tactile acuity, because it encourages training of the nonvisual senses to compensate for visual deprivation. Moreover, it was shown in the current study (Wong et al, 2011) that the ability of blind nonreaders was not statistically significantly better than sighted subjects, even though these blind nonreaders may have used their finger tactile sense for other purposes, such as object exploration and recognition, suggesting that blindness alone is not sufficient for the development of heightened sensory abilities. There is reason to believe, however, that visual deprivation can also directly lead to behavioral enhancements.…”
Section: Review Of Wong Et Alcontrasting
confidence: 58%
See 4 more Smart Citations
“…For instance, prior studies have shown that tactile finger acuity can increase in normal sighted individuals through intensive training (Sathian and Zangaladze, 1997;Harris et al, 2001), suggesting that blindness may only act as a facilitator in the development of increased tactile acuity, because it encourages training of the nonvisual senses to compensate for visual deprivation. Moreover, it was shown in the current study (Wong et al, 2011) that the ability of blind nonreaders was not statistically significantly better than sighted subjects, even though these blind nonreaders may have used their finger tactile sense for other purposes, such as object exploration and recognition, suggesting that blindness alone is not sufficient for the development of heightened sensory abilities. There is reason to believe, however, that visual deprivation can also directly lead to behavioral enhancements.…”
Section: Review Of Wong Et Alcontrasting
confidence: 58%
“…The findings of Wong et al (2011), along with those of previous research, raise interesting and important questions. Notably, is blindness a necessary prerequisite for the development of heightened sensory abilities?…”
Section: Review Of Wong Et Almentioning
confidence: 78%
See 3 more Smart Citations